(untitled) (Confluenţe Bibliologice, 2024)
This article provides a comprehensive report on the continuing professional training activities undertaken in 2024 by the staﬀ of the Scientiﬁc Library of USARB, in alignment with the institutional training policy. It emphasizes that continuous training of library staﬀ is a critical component for institutional success and signiﬁcantly impacts the quality of information and documentation services oﬀered. The article highlights the participation of 36 librarians in various training sessions, including formal training (549 academic hours), non-formal training organized by the institution (22 academic hours), and external non-formal training (859 academic hours), amounting to a total of 2,200 hours of continuous training. These activities were aimed at enhancing skills, supporting the eﬃcient management of information resources, and ensuring adaptability to ongoing changes in the ﬁeld.